ANALISIS PENJUALAN PRODUK KULINER MELALUI ONLINE PADA APLIKASI SOPHEE PLATFORM SOPHEEFOOD DI YOGYAKARTA - Evi Rosalina Widyayanti (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2022)
This study aims to analyze the sale of culinary products through online in businesses that make sales using the Shopee application platform SopheeFood in Yogyakarta. This research was conducted with a qualitative approach with triangulation data collection techniques consisting of interviews, observations and documents. Research data is limited from business actors residing in the city of Yogyakarta as a source of informants, business actors running culinary businesses, business actors using the ShopeeFood platform application, the research was conducted during April 2022. The data were obtained from two sources, namely primary data from direct interviews and observations and secondary data. from observations and documents. Interviews were conducted on 6 culinary businesses, namely 3 food culinary and 3 beverage culinary. The business sample appoints an authorized person as a research respondent who is assigned to be an informant as a valid and credible source. The six businesses were selected with several conditions, such as the limitations of research with a high rating on the Sophee Food platform, namely Siomay Mirza (Jl. Kapt P. Tendean), Rating 4.8, Mie Gacoan (Jl. Tamansiswa): Rating 4.9; Parikesit Balok Cake (Jl. Sisingamangaraja), Rating 4.9, Buy Coffee (Jl. Kapt. P. Tendean), Rating 4.9, Kopi Promise Jiwa (Jl. Suroto Kota Baru), Rating 4.9 and Couvee (Jl. KHA. Dahlan), Rating 4.9. The results of this study are able to answer research problems where SopheeFood is felt to be very effective for business actors in the city of Yogyakarta, the advantages of ShopeeFood are very helpful and facilitate sales, the existence of a promo strategy every day is an advantage that attracts consumers, the lack of ShopeeFood the application is still often error, slow/slow so that drivers are often difficult to find which interfere with the sales process, besides that some drivers still need further guidance, and the prospect of the shopeeFood platform in the future for business actors is very good because it is getting more and more users. Thus, it is necessary to pay attention to the Shopee Platform SopheeFood Application to make improvements in terms of the application and the Human Resources (HR) of the drivers who join.